Prevalence and Risk Factors for Hepatic Steatosis in Children With Perinatal HIV on Early Antiretroviral Therapy Compared to HIV-Exposed Uninfected and HIV-Unexposed Children - Rose, Penelope C.; Nel, Etienne D.; Cotton, Mark F.; Pitcher, Richard D.; Otwombe, Kennedy; Browne, Sara H.; Innes, Steve (Frontiers in Pediatrics, 2022)
Objectives We evaluated the prevalence and risk factors for hepatic steatosis in South African children with perinatally acquired HIV (PHIV) on long-term antiretroviral therapy (ART) compared to HIV-uninfected children. Design A cross-sectional study from April 2019 to October 2021. PHIV, HIV-exposed uninfected (HEU) and HIV-unexposed (HU) children were enrolled from an ongoing cohort study. Methods All children had transient elastography (TE) with controlled attenuation parameter (CAP). Liver enzymes, lipogram, insulin and glucose were sent after an overnight fast. Multivariable linear regression analyses identified predictors of CAP. Hepatic steatosis was defined as CAP>248kPa. Results 215 children (111 [52%] male; median age 14.1 years; IQR 12.7-14.9) participated in the study, 110 PHIV, 105 HIV-uninfected (36 HEU, 69 HU). PHIV initiated ART at a median age of 2.7 months (IQR 1.8-8.5). Hepatic steatosis prevalence was 9% in PHIV, 3% in HEU and 1% in HU children (p=0.08). However 8% of lean (body mass index z-score ≤+1) PHIV had hepatic steatosis compared to zero lean HEU or HU children (p=0.03). In multivariable linear regression analysis of all PHIV, body mass index (BMI) z-score was positively associated with CAP (p=0.001) while CD4 count (p=0.02) and duration of suppression of HIV viraemia (p=0.009) were negatively associated with CAP, adjusting for age, sex and ethnicity. Conclusions Hepatic steatosis prevalence was higher in lean PHIV than lean HIV-uninfected South African children. Longer suppression of HIV viraemia and higher CD4 count were associated with lower CAP and might be protective factors for hepatic steatosis in PHIV children.